Pengaruh total quality management terhadap kinerja perusahaan PT. Pos Indonesia (Persero) Denpasar 80000 - Antari, Luh Putu Rima; Setiawan, Putu Yudi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The growth of similar service companies is a challenge for the management in improving the company's performance, as an evaluation for its business ability to achieve the goals. One way operationally is to increase the implementation of Total Quality Management (TQM). The purpose of this study was to determine the effect of Total Quality Management on Company Performance at PT. Pos Indonesia (Persero) Denpasar 80000. Total Quality Management is viewed from 5 dimensions, namely customer focus, continuous improvement, teamwork, obsession with quality, and education and training. This research uses associative design and takes 77 employees of the company as the saturated sample, and is analyzed using multiple linear regression. The results show that the variables of TQM consisting of customer focus, continuous improvement, teamwork, obsession with quality, as well as education and training, positively have a significant influence on the company's performance at PT. Pos Indonesia (Persero) Denpasar 80000. The management is expected to further improve the company's performance through the implementation of Total Quality Management in competitive advantage.